THE INFLUENCE OF MEME CULTURE ON THE PERCEPTION OF JAPANESE MUSIC: A SURVEY OF DOLPHIN IN TOWN-KINGO HAMADA - Alfajri, Salsabila; Wibawarta, Bambang (International Review of Humanities Studies, 2025)
The research aims to explore the influence of meme culture on the perception of Japanese music in the digital era, specifically analyzing the impact of meme culture on the song "Dolphin in Town" by Kingo Hamada. This study utilized quantitative methods, with surveys as the main technique for data collection. The results showed that meme culture plays an important role in introducing songs and artists that may not have previously received attention. The study also highlights the diverse impacts of meme culture on the perception of Japanese music, including its influence on popularizing, accepting, and interpreting music in various ways. The research concludes that meme culture has become a significant force in shaping perceptions of music in the digital age, creating a social network in which music becomes a universal language, connecting people from different backgrounds, and enriching their musical experience.